Post Human - Deitch, Jeffrey; Castello di Rivoli, Museo d'Arte Contemporanea Rivoli (Torino); Deichtorhallen Hamburg; Deste Foundation for contemporary Art, Athens (Pully (Lausanne) : FAE Musée d'Art Contemporain, 1992)
This book explores the implications of genetic engineering, plastic surgery, mind expansion, and other forms of body alteration, to ask whether our society is developing a new model of the human being. It poses the question of whether our society is creating a new kind of post-human person that replaces previous constructions of the self. Images from the new technological and consumer culture and the new, conceptually oriented figurative art of thirty-six young artists will endeavor to give us a glimpse of the coming post-human world.
Adams, Dennis ; Antoni, Janine ; Armleder, John M. ; Balkenhol, Stephan ; Barney, Matthew ; Bickerton, Ashley ; Chiezo, Taro ; Clegg & Guttmann ; Delvoye, Wim ; Etkin, Suzan ; Fischli & Weiss ; Fleury, Sylvie ; Gober, Robert ; Gonzalez-Torres, Felix ; Hirst, Damien ; Honert, Martin ; Kelley, Mike ; Kilimnik, Karen ; Kippenberger, Martin ; Koons, Jeff ; Lappas, George ; Lemieux, Annette ; Marclay, Christian ; McCarthy, Paul ; Morimura, Yasumasa ; Nakahara, Kodai ; Noland, Cady ; Oates, Daniel ; Pruitt & Early ; Ray, Charles ; Ruff, Thomas ; Sherman, Cindy ; Smith, Kiki ; Stadtbäumer, Pia ; Vaisman, Meyer ; Wall, Jeff
biog. per kunstenaar
Engels
Post Human, FAE Musée d'Art Contemporain, Pully (Lausanne), 14 June to 13 September 1992 ; Castello di Rivoli, Museo d'Arte Contemporanea, Rivoli (Torino), 1 October to 22 November 1992 ; Deste Foundation for Contemporary Art, Athens, 3 December 1992 to 14 February 1993 ; Deichtorhallen, Hamburg, 12 March to 9 May 1993
boek